Identifying Genetic Variants for Heart Rate Variability in the Acetylcholine Pathway - Riese, Harriëtte; Muñoz, Loretto M.; Hartman, Catharina A.; Ding, Xiuhua; Su, Shaoyong; Oldehinkel, Albertine J.; van Roon, Arie M.; van der Most, Peter J.; Lefrandt, Joop; Gansevoort, Ron T.; van der Harst, Pim; Verweij, Niek; et al. (PloS one, 2014)
Heart rate variability is an important risk factor for cardiovascular disease and all-cause mortality. The acetylcholine pathway plays a key role in explaining heart rate variability in humans. We assessed whether 443 genotyped and imputed common genetic variants in eight key genes (CHAT, SLC18A3, SLC5A7, CHRNB4, CHRNA3, CHRNA, CHRM2 and ACHE) of the acetylcholine pathway were associated with variation in an established measure of heart rate variability reflecting parasympathetic control of the heart rhythm, the root mean square of successive differences (RMSSD) of normal RR intervals. The association was studied in a two stage design in individuals of European descent. First, analyses were performed in a discovery sample of four cohorts (n = 3429, discovery stage). Second, findings were replicated in three independent cohorts (n = 3311, replication stage), and finally the two stages were combined in a meta-analysis (n = 6740). RMSSD data were obtained under resting conditions. After correction for multiple testing, none of the SNPs showed an association with RMSSD. In conclusion, no common genetic variants for heart rate variability were identified in the largest and most comprehensive candidate gene study on the acetylcholine pathway to date. Future gene finding efforts for RMSSD may want to focus on hypothesis free approaches such as the genome-wide association study.